Association of Elevated Body Mass Index and Outcomes of Arthroscopic Treatment for Osteochondral Lesions of the Talus - Don Thong Siang Koh MBBS, BSc, MRCS; Marcus Wei Ping Tan MBBS, MRCS; Xia Zhan MBBS, MMed, FRCS; Zongxian Li MBBS, MMed, FRCS; Kae Sian Tay MBBS, MMed, FRCS; Shi Ming Tan MBBS, MMed, FRCS; Nicholas Eng Meng Yeo MBBS, MMed, FRCS; Inderjeet Rikhraj Singh MBBS, FRCS, MA (Foot & Ankle Orthopaedics, 2022)
Background: Osteochondral lesions of the talus (OLTs) are a common condition found in patients with chronic ankle pain after previous ankle sprains. Surgical management is indicated after conservative management has failed. Hypothesis/Purpose: This study evaluates the influence of body mass index (BMI) on the early clinical outcomes of arthroscopic debridement and microfracture of OLTs. Methods: A total of 252 patients with symptomatic OLTs who failed conservative management underwent arthroscopic debridement and microfracture of OLTs over the affected ankle between 2007 and 2017. Patients from this cohort were divided into 2 groups based on BMI: the normal BMI group (NB Group) (BMI 18.5-25.0) and overweight and obese BMI group (OB Group) (BMI ≥25). Visual analogue scale (VAS), American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score, and the physical and mental component summaries of the 36-Item Short-Form Health Survey (PCS and MCS, respectively) were prospectively collected from the cohort during their standard postoperative outpatient follow-up. Results: The NB Group (n=105) and OB Group (n=147) were well matched demographically. The operative duration was significantly shorter for the NB Group compared to the OB Group. Patients from both groups had significant improvements in VAS, AOFAS, and PCS scores postoperatively at 6 and 24 months after surgery ( P < .05). Between both groups, patients had comparable VAS, AOFAS, and PCS scores at preoperation, 6 months postoperation, and 24 months postoperation ( P > .05). However, MCS in the OB Group was lower at 24 months postoperatively compared with the NB Group ( P < .05). The OB Group reported better satisfaction scores (82.4% vs 72.6%, P < .05), and a greater proportion had their expectations met (88.2% vs 77.9%, P < .05). Conclusion: A BMI ≥25 was not associated with worse postoperative pain and functional outcomes, but rather was found to be associated with greater satisfaction and fulfillment. However, patients with BMI ≥25 required longer procedure duration and had poorer MCS scores at 24 months after surgery. Level of Evidence: Level III, retrospective cohort study.